Trichoderma application methods differentially affect the tomato growth, rhizomicrobiome, and rhizosphere soil suppressiveness against Fusarium oxysporum - Bandara, Ananda Y.; Kang, Seogchan (Frontiers in Microbiology, 2024)
Trichoderma spp. are widely used to enhance crop growth and suppress diverse diseases. However, inconsistent field efficacy remains a major barrier to their use as a reliable alternative to synthetic pesticides. Various strategies have been investigated to enhance the robustness of their application.Here, we evaluated how T. virens application methods (pre-, at-, and post-transplant) affect the growth of two tomato varieties and their rhizosphere fungal and bacterial communities. Although the greatest rhizosphere abundance of T. virens was observed in the post-transplant application, the at-transplant application promoted tomato growth the most, indicating that greater rhizosphere abundance does not necessarily result in better tomato growth. None of the application methods significantly altered the global rhizosphere fungal/ and bacterial community communities of composition, indicating the non-adverse effect of T. virens on the native rhizomicrobiomes of the tested varieties. Changes in specific microbial genera and guilds may underpin the enhanced tomato growth. We also investigated whether the resulting microbiome changes affect the mycelial growth and conidial germination of Fusarium oxysporum f. sp. lycopersici and F. oxysporum f. sp. radicis-lycopersici, soilborne fungal pathogens of tomato, upon exposure to volatile compounds emitted by culturable rhizosphere microbes and metabolites extracted from the rhizosphere soils after Trichoderma treatments. Volatile compounds produced by cultured rhizosphere microbes after the at-transplant application suppressed the mycelial growth of both pathogens the mostbetter than those after the other treatments. Similarly, the water-soluble metabolites extracted from the rhizosphere soil samples after the at-transplant application most effectively better suppressed their conidial germination rate of F. oxysporum spores. Overall, our study results suggests that the attransplant application is most advantageous for promoting the growth of the tested tomato varieties and building soil suppressiveness against the tested fusaria. Further However, further studies studies are needed before applying this method to support tomato production. We discuss critical future questions. are needed to understand how different Trichoderma species, tomato varieties, and soil types modulate tomato growth and rhizomicrobiomes, and how the resulting rhizomicrobiome changes contribute to the suppression of various soilborne pathogens.